The effect of laminin-1-doped nanoroughened implant surfaces: Gene expression and morphological evaluation - Schwartz-Filho, Humberto Osvaldo; Bougas, Kostas; Coelho, Paulo G.; Xue, Ying; Hayashi, Mariko; Faeda, Rafael Silveira [UNESP]; Marcantonio, Rosemary Adriana Chierici [UNESP]; Ono, Daisuke; Kobayashi, Fumio; Mustafa, Kamal; Wennerberg, Ann; Jimbo, Ryo (Hindawi, 2012)
Aim. This study aimed to observe the morphological and molecular effect of laminin-1 doping to nanostructured implant surfaces in a rabbit model. Materials and Methods. Nanostructured implants were coated with laminin-1 (test; dilution, 100 g/mL) and inserted into the rabbit tibiae. Noncoated implants were used as controls. After 2 weeks of healing, the implants were removed and subjected to morphological analysis using scanning electron microscopy (SEM) and gene expression analysis using the real-time reverse transcriptase-polymerase chain reaction (RT-PCR). Results. SEM revealed bony tissue attachment for both control and test implants. Real-time RT-PCR analysis showed that the expression of osteoblast markers RUNX-2, osteocalcin, alkaline phosphatase, and collagen I was higher (1.62-fold, 1.53-fold, 1.97-fold, and 1.04-fold, resp.) for the implants modified by laminin-1 relative to the control. All osteoclast markers investigated in the study presented higher expression on the test implants than controls as follows: tartrate-resistant acid phosphatase (1.67-fold), calcitonin receptor (1.35-fold), and ATPase (1.25-fold). The test implants demonstrated higher expression of inflammatory markers interleukin-10 (1.53-fold) and tumour necrosis factor-α (1.61-fold) relative to controls. Conclusion. The protein-doped surface showed higher gene expression of typical genes involved in the osseointegration cascade than the control surface. © 2012 Humberto Osvaldo Schwartz-Filho et al.